2007
DOI: 10.1021/jp076730b
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Synthesis and Pseudocapacitance Properties of α-MnO2 Hollow Spheres and Hollow Urchins

Abstract: MnO 2 hollow spheres and hollow urchins are synthesized via a simple hydrothermal process without using any template or organic surfactant. The effect of the reaction time on the microstructure and morphology of samples is observed systemically. Meanwhile, the forming mechanism of hollow-structured R-MnO 2 is carefully investigated by using field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), and high-resolution transmission electron microscopy (HRTEM). The results of ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
298
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 501 publications
(314 citation statements)
references
References 26 publications
14
298
2
Order By: Relevance
“…This pattern matched that of the CV results, and in comparison with previous reports on hollow-structured manganese oxides, the specific capacitance for CMHS produced via CV and galvanostatic cycling are quite competitive. Previously reported values include: hollow MnO2 spheres of 115 F g -1 at 0.5 A g -1 in 1 M Na2SO4 electrolyte 14 ; double-shelled MnO2 hollow spheres of 210.2 F g -1 at 0.2 A g -1 in 1 M Na2SO4 electrolyte 22 ; hollow α-MnO2 of 167 F g -1 at 2.5 mA cm -2 in 1 M Na2SO4 electrolyte 18 ; and nano-structured MnO2 hollow spheres of 147 F g -1 at 0.2 A g -1 in 1-butyl-3-methylimidazolium hexaurophosphate in DMF electrolyte 41 . However, MnO2 hollow paramecium of 554.3 F g -1 at 1 A g -1 21 and hollow tubular MnO2 of 315 F g -1 at 0.2 A g - 1 19 are the exceptionally high examples in the field.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…This pattern matched that of the CV results, and in comparison with previous reports on hollow-structured manganese oxides, the specific capacitance for CMHS produced via CV and galvanostatic cycling are quite competitive. Previously reported values include: hollow MnO2 spheres of 115 F g -1 at 0.5 A g -1 in 1 M Na2SO4 electrolyte 14 ; double-shelled MnO2 hollow spheres of 210.2 F g -1 at 0.2 A g -1 in 1 M Na2SO4 electrolyte 22 ; hollow α-MnO2 of 167 F g -1 at 2.5 mA cm -2 in 1 M Na2SO4 electrolyte 18 ; and nano-structured MnO2 hollow spheres of 147 F g -1 at 0.2 A g -1 in 1-butyl-3-methylimidazolium hexaurophosphate in DMF electrolyte 41 . However, MnO2 hollow paramecium of 554.3 F g -1 at 1 A g -1 21 and hollow tubular MnO2 of 315 F g -1 at 0.2 A g - 1 19 are the exceptionally high examples in the field.…”
mentioning
confidence: 96%
“…Hollownanostructured manganese oxides are attractive due to the high abundance, environmental friendliness and high theoretical specific capacity of manganese oxides 2,[14][15][16][17] . Various studies have reported hollow MnO2 structures such as spheres [14][15][16]18 , tubes 19 , urchin 20 , and paramecium 21 , prepared using methods employing oxidationetching and hard-templates. These hollow-structured MnO2 crystals have a specific capacitance range of ~100 to 300 F g -1 at current densities lower than 2 A g -1 .…”
mentioning
confidence: 99%
“…At higher scan rate, ions to access all available active sites have difficulty as anion doping/undoping reactions cannot be completely fulfilled. 34 Generally, the SC value of active electrode is the highest at its lowest scan rate, and therefore, in PANI-NRs, an SC of 598 F/g was obtained at scan rates of 5 mV/s ͑Fig. 4b͒.…”
Section: A168mentioning
confidence: 99%
“…To address these problems, a templet free design of 3D open architecture process has been developed [19][20][21].MnO2in the shape of micro-flower have been considered as one of the optimal nanostructure because of the fully exposed structure/high surface area which can facilitate the transportation of electrons and cations. But the synthesis of flower like architecture still faces a challenge owing to the fast and complex growing process.…”
Section: Introductionmentioning
confidence: 99%